Sensitivity Analysis of the Dominant Design Parameters of Supersonic Separators for Gas Compositions - K. Ghorbanian; M.R. Amini Magham (مهندسی مکانیک شریف, 2021)
Separation of mixtures, gases, and phases is of great industrial importance. Various methods and equipment are utilized for the separation. One of the most novel and innovative as well as efficient methods is supersonic separation where acceleration of the flow mixture is accompanied by fast reduction in temperature and pressure. As a consequence, heavier components which have a higher condensation temperature will liquefy faster than lighter components. Swirling flow and centrifugal force will drive heavier condensed droplets toward the outer wall and separate them from lighter components in the gas phase. In general, supersonic separators consist of a converging-diverging nozzle and a cyclone separator. Due to no moving or rotating parts, supersonic separators have high reliability, long endurance, easy manufacturing, and less expensive operation and maintenance. In this paper, the one-dimensional design of a supersonic separator for separation and purifying of Methane from natural gas mixture is presented. Since separation process is in vicinity of saturation line, real gas model from NIST REFPROP software is used to estimate the fluid thermodynamic properties. For the design of cyclone separator and phase separations, instantaneous nucleation at the nozzle discharge is assumed and displacement of smallest droplet (as the worst case) is only considered. After calculating the supersonic separator geometry, performance sensitivity to changes in inlet temperature, pressure, and gas composition is studied, the effectiveness of these parameters is compared and rate of performance change is calculated. At next step, the simultaneous change of the inlet conditions is investigated and effect of each parameter on the effectiveness of others is studied. Finally, in order to optimize phase separation in various operating conditions, effects of swirler angle and swirl intensity on separation length are studied and optimum swirl intensity to gain the best possible separation performance with a fixed geometry separator for different inlet conditions is determined.